3112 Factors Associated with Hesitancy of Human Papillomavirus Vaccination Among Latina Immigrant Mothers Despite Physician Recommendation. (27th March 2019) - Khodadadi, Alexandra B; Redden, David; Scarinci, Isabel
Abstract : OBJECTIVES/SPECIFIC AIMS: The purpose of this study was to examine factors associated with Latina immigrant mothers' hesitancy in having their 9-12 year old daughters vaccinated against HPV despite a physician recommendation. METHODS/STUDY POPULATION: The data analyzed for this study was from a previous effort that examined the efficacy of an intervention to promote HPV vaccination among daughters (9-12 years of age) of Latina immigrants (N=317) through a randomized trial. Baseline data among Latina immigrant mothers with unvaccinated daughters was collected prior to this intervention. Participants were surveyed on sociodemographic characteristics, knowledge and perceptions of cervical cancer and HPV, and intention to vaccinate their daughters with the HPV vaccine if recommended by the daughter's physician. RESULTS/ANTICIPATED RESULTS: Out of 317 participants, 205 reported willingness to vaccinate following a physician recommendation (64.7%) while 112 reported hesitancy (defined as an answer of "maybe") to vaccinate their daughters (35.3%). None of the participants indicated "no". No sociodemographic factors were significantly associated with vaccine hesitancy except for the daughter's health insurance status (p = 0.03). A significant difference existed in the mother's perceived risk of cervical cancer in herself based on hesitancy and willingness to vaccination (p < 0.001). Mother's awareness of HPV (p < 0.0001), knowledge of HPV (p < 0.01), her perceived risk of HPV infection in herself (p < 0.01) and in her daughter (p < 0.0001), and her worry about her daughter being infected with HPV (p = 0.02) were also significant. Finally, there were differences among mothers in confidence of being able to have their daughters complete all three doses of the vaccine (p < 0.0001), and having the time (p < 0.0001) and the money (p < 0.0001) to complete the vaccination series. Factors that were significant in the univariate analysis were then incorporated into a binary logistic multivariable regression. HPV knowledge score was excluded from this analysis due to its limited sample size (n = 169). The five variables that were strongly associated with the outcome of vaccine hesitancy included: HPV awareness, mother's perceived risk of HPV infection in their daughter, confidence in the ability to receive all three shots in vaccine series, confidence in being able to afford the vaccine series, and daughter's health insurance. All were positively correlated with intention to vaccinate except for daughter's health insurance status. DISCUSSION/SIGNIFICANCE OF IMPACT: Despite research showing Latinos are pro-vaccination and the association between HCP provider recommendation and vaccine acceptability among parents, over 35% of Latina immigrant mothers in our study were still hesitant about having their daughters vaccinated against HPV following a physician recommendation. Factors that strongly contributed to this hesitancy included HPV awareness, mother's perceived risk of their daughter being infected with HPV, self-efficacy (ability to receive all required shots and finding time to complete the HPV vaccination series), and daughter's health insurance status. These results indicate that HCP recommendation may be not enough of a driving factor to motivate Latina immigrant mothers to vaccinate their daughters against HPV. Further research efforts should focus on heightening perceived risk of HPV infection, improving knowledge of HPV, and boosting their self-efficacy to get their children vaccinated against HPV.